COMPARISON BETWEEN DUPUIS AND PANJABI METHODS IN CALCULATING TRANSLATION AND ROTATION OF LUMBAR VERTEBRAE IN FLEXIONEXTENSION RADIOGRAPHY - MT Taghipour Darzi, (Babol University of Medical Sciences, 2008)
BACKGROUND AND OBJECTIVE: Different ideas have proposed for translation and rotation values of lumbar vertebrae in sagittal plane that is a challenge for physicians. Calculating method can be one of the difference sources. Of the proposed methods, two common methods are Dupuis and Panjabi methods that have very similarity. Therefore the objective of this study was to compare these two methods. METHODS: There were 66 males aged between 20-45 years participated in this study. Radiographic variables contain vertebral translation and rotation in sagittal plane which were calculated with Dupuis and Panjabi methods. The Putto method was used for flexion – extension radiography. Three radiographies were taken in neutral, full flexion and full extension positions. The variables were calculated using CARA software after scanning. FINDINGS: Results demonstrated that the mean differences between two methods for translation of L1 (p=0.19), L2 (p=0.15), L3 (p=0.12), L4 (p=0.89) segments were not significant. The mean differences between two methods for rotation of L1 (p=0.13), L2 (p=0.32), L3 (p=0.08), L4 (p=0.11) segments were not significant. In addition, the correlation of variables between two methods in lumbar segments was high. CONCLUSION: There was not a significant difference between Dupuis and Panjabi methods in calculation of lumbar vertebral translation and rotation. However, calculating translation and rotation of L5 vertebra is not possible using Dupuis method, utilization of Panjabi method would have a better result in clinical point of view.